2019
DOI: 10.4158/accr-2018-0388
|View full text |Cite
|
Sign up to set email alerts
|

Pruritic Rash in an Elderly Patient with Uncontrolled Diabetes Mellitus

Abstract: Objective: Acquired reactive perforating collagenosis is an uncommon skin disease that belongs to a group of dermatologic disorders characterized by transepidermal elimination of dermal material. It is highly associated with systemic disease, primarily diabetes mellitus and dialysisdependent chronic renal failure. Methods: A 70-year-old female with 20 years of poorly controlled type 2 diabetes mellitus presented with a 6-month history of multiple pruritic erythematous papules and nodules with central hyperkera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…[28] Seborrheic keratosis described as a proliferation of clonal keratinocytes and melanocytes, as incidence is in the range of 10-70% of HZ cases. [5,13,26] In this study, PHN cases were found as much as 0.93% of subjects.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…[28] Seborrheic keratosis described as a proliferation of clonal keratinocytes and melanocytes, as incidence is in the range of 10-70% of HZ cases. [5,13,26] In this study, PHN cases were found as much as 0.93% of subjects.…”
Section: Methodsmentioning
confidence: 49%
“…Another factor that may contribute to this condition is the use of certain ingredients as allergens such as lanolin, paraben esters, dyes, plants, balm, rubber, nickel and topical therapy. [3,26,27] This study found basal cell carcinoma in 0.…”
Section: This Study Used Primary Data On 80 Patients Who Visited the mentioning
confidence: 61%
“…An interesting visual vignette described a skin rash seen in patient with type 1 diabetes mellitus due to elevated triglyceride levels. 6 You can probably figure what the rash might be?…”
mentioning
confidence: 99%